"Synthesis and Study of Azo based Liquid Crystals: Effect of the lateral bromo and terminal alkoxy side chain on Thermal, Mesomorphic and Optical properties". (11th February 2019) - Jadeja, Upendra.H.; Sharma, Vinay S.; Prajapat, Varsha; Shah, Akshara; Sharma, Anuj S.
Abstract: An azoester based calamitic shaped LCs material has been synthesized and studied their optical and thermal properties. The present synthesized derivatives having terminally substituted –OR and –OC6 H13 (n) groups on both the end side including ester and azo linking groups. All the synthesized derivatives displayed enantiotropical nematic and SmC phase with good temperature range which is influenced by the substitution of the alkyl chain on alkoxy group. The observed texture images of present synthesized compounds are fan, needle and droplets type which were measured by POM equipped with heating stage. All this compounds were characterized by FT-IR, 1 H NMR analysis. The mesomorphism is measured by POM, DSC and the molecular packing is further confirmed by XRD technique. The relationship between structure and mesomorphic properties was discussed in framework of geometrical configuration of central linking unit and molecular length with addition of lateral substituted bromo group which affect the interaction of the molecules. Photosensitive azobenzene group undergoes photoisomerisation under UV light Graphical Abstract: